PERAN GURU DALAM MENGEMBANGKAN KETERAMPILAN KOMUNIKASI SISWA KELAS V-A DI MI CHAIRIYAH MANSURIYAH JAKARTA BARAT - Fahrijal, Ahmad; Al-Nur, Widya Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
This study aims to illustrate the role of teachers in the development of communication skills of students in grade 5A of MI Chairiyah Mansuriyah. Research data were obtained through a triangulation process consisting of analysis of observational data, interviews, and documentation of learning activities related to the research topic. Based on these data, researchers discovered an important role for teachers in developing students' communication skills. Teachers as role models or role models, Teachers as Motivators, Teachers as guides, Teacher as facilitator, and Teacher as educator..